E-business and telecommunications : 6th international joint conference, ICETE 2009, Milan, Italy, July 7-10, 2009 : revised selected papers - Obaidat, Mohammad S. (Mohammad Salameh); Filipe, Joaquim (Communications in computer and information science, 2011)
This book constitutes the refereed proceedings of the 6th International Joint Conference on e-Business and Telecommunications, ICETE 2009, held in Milan, Italy, in July 2009. The 34 revised full papers presented together with 4 invited papers in this volume were carefully reviewed and selected from 300 submissions. They have passed two rounds of selection and improvement. The papers are organized in topical sections on e-business; security and cryptography; signal processing and multimedia applications; wireless information networks and systems.